Biological characteristics of Alternaria solani fungal pathogen - Yuldosheva Zebo; Sodikov Bakhrom; Khamirayev Ural; Makamov Abdusalom (BIO Web of Conferences)
The Alternaria genus is found in various regions of the world. One economically significant member of this genus is Alternaria solani, which causes early blight disease in potatoes and tomatoes. Early blight affects the leaves, stems, and tubers of potatoes. The symptoms on leaves usually appear 5–20 days before flowering as brown or dark brown spots, often surrounded by concentric rings. Studying the biological characteristics of the pathogenic fungus is essential for effective protection of potatoes against early blight. This article presents the results of our laboratory studies on the biological characteristics of Alternaria fungi isolated from infected potato plants.